Compound Histories Materials, Governance and Production, 1760-1840 - Roberts, Lissa; Werrett, Simon (Cultural Dynamics of Science, 2017)
Compound Histories: Materials, Governance and Production, 1760-1840 explores the intertwined realms of production, governance and materials, placing chemists and chemistry at the center of processes most closely identified with the construction of the modern world. Readership: All interested in European history since the mid-eighteenth century, and anyone interested in the history of industrialization, science, technology, modernization, political economy, environmental history, materials and governance.